Expressing uncertainty in criminology: Applying insights from scientific communication to evidence-based policing - Giacomantonio, Chris (Criminology & criminal justice, 2024)
Scholars and practitioners who develop evidence-based crime policy debate on how best to translate criminological knowledge into better criminal justice practices. These debates highlight the counterpoised problems of over-selling the contribution of scientific evidence; or, alternately, overemphasizing the limitations of science. This challenge attends any attempt to translate research findings into practice; however, and problematically, in criminology this challenge is rarely approached in a theoretically coherent fashion. This article therefore seeks to theorize uncertainty in criminology by examining insights on communicating scientific uncertainty in other fields, and applying these insights specifically to the field of Evidence-Based Policing (EBP). Taking the position that all science is inherently uncertain, we examine the following four aspects of the field: the particular uncertainties of criminology, variance in receptivity to research, the lack of evidence regarding effective communication, and the boundaries of evidence. Building on this analysis, we set out the normative challenge of how researchers should characterize and balance the implications and limits of scientific findings in the decision-making process. Looking ahead, we argue for the need to invest in an empirical project for determining meaningful strategies to express research evidence to decision-makers.